Cardiorespiratory fitness is an important marker of cognitive performance in older Latin Americans - Johnson, David K. (2023)
Background: Our previous research with older non-Hispanic whites demonstrated that with increasing cardiorespiratory fitness (CRF) there was a concomitant linear increase in processing speed (PS) performance. PS has also been found in a number of reports as a potential precursor to memory decline associated with Alzheimer’s disease and cognitive aging. The purpose of this study was to examine whether the same cognitive benefits imbued by CRF generalize within a healthy Latino aging community living in Costa Rica (CR). Method: 415 community dwelling older adults (315 CR and 100 non-Hispanic whites living in the United States) with a mean age of 71 (SD = 5.29) years old were recruited from the Epidemiology and Development of Alzheimer’s Disease (EDAD), a large international study of Latino cognitive aging. Participants completed neuropsychological testing and a graded treadmill exercise stress test. We compared the relationship between Oxygen Uptake Efficiency Slope (OUES) and a composite measure of PS (Digit Symbol, Block Design, and Stroop Color Naming). Confirmatory factor analysis was conducted. Result: CRF (OUES) significantly predicted PS within the CR (B = 0.50; p < .001) group and non-Hispanic white (B = 0.25; p < .05) group after controlling for age and sex. The relationship between CRF and the PS factor showed a non-significant misfit when the relationship was constrained to be equal on both groups (χš (1) = 0.39, p = 0.53), hence the relationship is equivalent between groups. Conclusion: In a healthy sample of older individuals living in CR we found the same score profile and interrelationships that were identified among non-Hispanic whites living in the United States. CRF and PS are clinically meaningful therapeutic targets for dementia prevention among older Latin Americans.